Cobalt single-atoms anchored on porphyrinic triazine-based frameworks as bifunctional electrocatalysts for oxygen reduction and hydrogen evolution reactions. Issue 3 (21st December 2018) - Yi, Jun-Dong; Xu, Rui; Chai, Guo-Liang; Zhang, Teng; Zang, Ketao; Nan, Bing; Lin, Hua; Liang, Yu-Lin; Lv, Jiangquan; Luo, Jun; Si, Rui; Huang, Yuan-Biao; et al.
Abstract : Cobalt single atoms anchored on porphyrinic triazine frameworks exhibit high activity in ORR and HER. Abstract : Designing and fabrication of highly active single-atom catalysts (SACs) with maximized atomic efficiency is highly desirable but still remains a great challenge. Herein, highly active and stable cobalt single-atoms with a Co–N4 moiety were uniformly anchored on a porous porphyrinic triazine-based framework (CoSAs/PTF) by a simple ionothermal method. Due to the abundant single-atom Co–N4 species, the hierarchical porous structure and the good conductivity, the resultant catalyst is highly active for the electrocatalytic oxygen reduction reaction (ORR) and hydrogen evolution reaction (HER). For the ORR, a more positive half-wave potential of 0.808 V ( vs. RHE) was achieved, compared with commercial benchmark Pt/C (0.806 V). Furthermore, a small onset potential of 21 mV and a low Tafel slope of 50 mV per decade were obtained for the HER. The porphyrin-like structure was found to stabilize the CoSAs effectively, thus leading to long-term durability and a remarkable methanol-tolerant behavior. This bifunctional single-atom catalyst might be a promising candidate to replace Pt-based electrocatalysts in electrolysers and fuel cells.